Positive electrode active material, its manufacturing method, and positive electrode including same
By aligning the long axis of crystal grains and lithium mobility routes in single particle-shaped positive electrode active materials through controlled firing and mixing processes, the battery's initial resistance and life characteristics are improved, addressing the separation issues of secondary particles in lithium secondary batteries.
Patent Information
- Application Number
- JP2024543358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-22
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The separation of secondary particles formed by aggregation of primary particles in positive electrode active substances during charging and discharging in lithium secondary batteries leads to a decrease in battery life characteristics, capacity, and output, necessitating improved alignment of the C-axis direction of single particle-shaped positive electrode active materials.
The production of single particle-shaped positive electrode active materials involves primary and secondary firing processes in an oxygen atmosphere, with specific temperature controls and mixing ratios to align the long axis of crystal grains and lithium mobility routes, ensuring a value of α (cosα) ≥ 0.5 and θ (cosθ) ≥ 0.6, enhancing the alignment of these directions.
This alignment improves the initial resistance and life characteristics of batteries by ensuring the C-axis direction of the positive electrode active material is aligned vertically to the electrode surface, thereby enhancing battery performance.
Smart Images

Figure 2025503094000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0062284, filed on May 20, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a single-particulate positive electrode active material, a method for producing the same, and a positive electrode including the same. [Background technology]
[0003] In recent years, with increasing technological development and demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources has increased dramatically. In general, a lithium secondary battery is composed of a positive electrode, a negative electrode, a separator, and an electrolyte, and the positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions.
[0004] On the other hand, the positive electrode active material used in lithium secondary batteries generally has a spherical secondary particle shape formed by agglomeration of several hundred fine primary particles of submicron size. However, the secondary particle positive electrode active material has a problem that the agglomerated primary particles are separated during repeated charging and discharging, causing the secondary particles to crack, resulting in a deterioration of battery characteristics.
[0005] In order to solve such problems, development of single-particle positive electrode active materials has been actively carried out, but when an electrode is manufactured using a single-particle positive electrode active material, it is difficult to align the c-axis direction, which is the main expansion direction of the single-particle positive electrode active material, as desired or to quantify the degree of alignment. On the other hand, when the c-axis direction, which is the main expansion direction of the single-particle positive electrode active material, is not aligned but exists randomly, problems such as deterioration of battery life characteristics, capacity reduction, and output reduction occur. Therefore, a technology to overcome this is indispensable. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a single-particulate positive electrode active material capable of realizing a battery having improved initial resistance characteristics and life characteristics, a method for producing the same, and a positive electrode including the same. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides a single-particulate positive electrode active material, a method for producing the same, and a positive electrode including the same. (1) In the present invention, the angle between the long axis of the crystal grain obtained by EBSD analysis and the lithium migration path is defined as α, and the angle is (cosα) 2 The present invention provides a single-particle positive electrode active material having a particle size distribution of 0.5 or more.
[0008] (2) In the present invention, there is provided the single-particle positive electrode active material according to (1) above, which is composed of 1 to 50 single crystal particles. (3) In the present invention, the single crystal particles have an average particle size (D EBSD ) is 0.1 μm to 10 μm.
[0009] (4) The present invention provides a method for producing a single-particulate positive electrode active material, comprising the steps of: (A) mixing a positive electrode active material precursor and a lithium raw material, and primarily baking the mixture at a temperature of 800°C to 1000°C to produce a plastic product, and then secondary baking the plastic product at a temperature lower than the primary baking temperature to produce a single-particulate lithium transition metal oxide; (B) mixing the single-particulate lithium composite transition metal oxide with a cobalt raw material to prepare a mixture; and (C) heat-treating the mixture at a temperature of 650°C to 800°C.
[0010] (5) The present invention provides the method for producing a single-particle positive electrode active material according to (4) above, wherein the primary firing in step (A) is carried out in an oxygen atmosphere. (6) The present invention provides the method for producing a single-particle positive electrode active material according to (4) or (5) above, wherein the secondary baking in step (A) is carried out at a temperature of 700°C to 900°C.
[0011] (7) The present invention provides the method for producing a single-particle positive electrode active material according to any one of (4) to (6) above, wherein the secondary baking in step (A) is carried out in an oxygen atmosphere.
[0012] (8) The present invention provides the method for producing a single-particulate positive electrode active material according to any one of (4) to (7) above, wherein in the step (B), the single-particulate lithium transition metal oxide and the cobalt raw material are mixed in a molar ratio of 1:0.0001 to 0.05.
[0013] (9) The present invention provides the method for producing a single-particulate positive electrode active material according to any one of (4) to (8) above, wherein the mixing in the step (B) is dry mixing.
[0014] (10) The present invention provides the method for producing a single-particle positive electrode active material according to any one of (4) to (9) above, wherein the heat treatment in step (C) is carried out in an oxygen atmosphere.
[0015] (11) The present invention provides a positive electrode including a current collector and a positive electrode active material layer located on the current collector, the positive electrode active material layer including the single-particle positive electrode active material according to the present invention.
[0016] (12) In the present invention, when the angle between the lithium migration path of the single particle positive electrode active material and an axis parallel to the upper surface of the current collector is θ, (cosθ) 2 The positive electrode according to (11) above, wherein the value is 0.6 or more. (13) The present invention relates to the (cosθ) 2 value and (cosα) 2The positive electrode according to (11) or (12) above, wherein the difference in value is 0.2 or less. Effect of the Invention
[0017] The positive electrode active material according to the present invention has a single particle shape in which the major axis of the crystal grains and the lithium migration path are aligned parallel to each other, and can improve the initial resistance characteristics and life characteristics of a battery containing it. [Brief description of the drawings]
[0018] [Figure 1] 1 is an EBSD Band Contrast (BC) image of a cross section of a positive electrode including the positive electrode active material of Example 1. [Diagram 2] FIG. 2(a) is an SEM image of a cross section of a positive electrode including the positive electrode active material of Comparative Example 1, and FIG. 2(b) is an EBSD Band Contrast (BC) image of a cross section of a positive electrode including the positive electrode active material of Comparative Example 1. [Diagram 3] FIG. 1 is a diagram showing the angle between the c-axis vector (Euler angle) of a crystal grain and a vector perpendicular to the electrode (= the angle between the lithium migration path (Li path) and a vector parallel to the electrode). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0020] It should be understood that, as used herein, terms such as "comprises," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.
[0021] In this specification, the term "on" is meant to include not only the case where one structure is formed directly on top of another structure, but also the case where a third structure is interposed between the structures.
[0022] In this specification, the term "single-particle positive electrode active material" is a concept that is contrasted with a spherical secondary particle positive electrode active material formed by agglomeration of several hundred primary particles produced by a conventional method, and means a positive electrode active material consisting of 50 or less single crystal particles. Specifically, the single-particle positive electrode active material in the present invention may be one single crystal particle, or may be in the form of an aggregate of 2 to 50, 2 to 40, 2 to 30, 2 to 20, 2 to 15, 2 to 10, or 2 to 5 single crystal particles. In this case, the "single crystal particle" means the smallest unit of a particle that can be recognized when observing the positive electrode active material with a scanning electron microscope.
[0023] In this specification, the average particle size (D 50 ) means the particle size at 50% of the volume cumulative particle size distribution of the positive electrode active material precursor, the positive electrode active material, or the lithium transition metal oxide powder. 50 ) can be measured using the laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W. After obtaining a graph of the volume cumulative particle size distribution, the particle size corresponding to 50% of the volume cumulative amount can be measured.
[0024] In this specification, the average grain size of the single crystal grains (D EBSD ) refers to the particle size at 50% of the volume cumulative particle size distribution of single crystal particles obtained by EBSD analysis using SEM. The EBSD analysis can be performed by obtaining an image through a SEM-EBSD device (e.g., FEI Quanta200-EDAX Velocity super OIM 8) and analyzing the image using image analysis software (EDAX OIM Analysis). The present invention will be described in detail below.
[0025] positive electrode active material In the present invention, when the angle between the long axis of the crystal grain obtained by EBSD analysis and the lithium migration path is α, (cosα) 2 The present invention provides a single-particle positive electrode active material having a particle size distribution of 0.5 or more.
[0026] The long axis of the crystal grain means the longest line segment among the line segments that pass through the center of gravity of the crystal grain and are cut by the crystal grain, and the lithium migration path means the path along which lithium ions move and means the direction perpendicular to the c-axis direction vector of the crystal grain.
[0027] The angle between the long axis of the crystal grain and the lithium migration path can be obtained by EBSD analysis of samples such as a powder of a positive electrode active material and a cross section of a positive electrode containing a positive electrode active material. For example, it can be obtained by measuring and analyzing a cross section of a positive electrode containing a positive electrode active material using JEOL's JSM-7900F (accelerating voltage: 20 kV). In this case, AztecCrystal from OXFORD Instruments can be used as image processing-EBSD quantification analysis software. Meanwhile, since the angle between the long axis of the crystal grain and the lithium migration path is a relative value, it is considered that it is not affected by the device used, the measurement conditions, etc.
[0028] The present inventors have discovered that the positive electrode active material is in the form of a single particle and has the above (cosα)2 When the value is 0.5 or more, the contraction / expansion direction of the positive electrode active material during the electrode manufacturing process (rolling, etc.) is aligned perpendicular to the upper surface of the current collector (or the electrode surface), and the lithium migration path is aligned parallel to the electrode surface, improving the performance of the battery including the same, particularly the initial resistance characteristics and life characteristics. Based on this finding, the present invention has been completed. 2 The value may be greater than or equal to 0.5, 0.55, or 0.6 and less than or equal to 0.8, 0.9, or 1.
[0029] On the other hand, the above (cosα) 2 If the value is less than 0.5, the contraction / expansion direction of the positive electrode active material during the electrode manufacturing process (rolling, etc.) is aligned parallel to the electrode surface, resulting in a problem of reduced initial resistance characteristics and life characteristics of the battery.
[0030] The single particle positive electrode active material has an average particle size (D 50 Specifically, the average particle diameter (D 50 ) may be 0.1 μm, 1.0 μm, or 2.0 μm or more, and 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, or 10.0 μm or less. In this case, the rolling ratio of the battery including the single-particle positive electrode active material can be increased, and the battery performance can be further improved.
[0031] According to the present invention, the single-particle positive electrode active material may be composed of 1 to 50 single crystal particles according to the contraction / expansion direction of the positive electrode active material and the arrangement of the lithium transfer path. Specifically, the single-particle positive electrode active material may be composed of 1 or more, 5, 10, 20, 30, 40, or 50 or less single crystal particles.
[0032] According to the present invention, the single crystal particles have an average particle size (D EBSD) may be 0.1 μm to 10 μm, specifically 0.1 μm or 0.2 μm or more and 5 μm, 8 μm, or 10 μm or less. In this case, it is possible to prevent the slurry (composition for forming a positive electrode active material layer) from coagulating or gelling during the production of the electrode, and it is possible to reduce the occurrence of cracks in the particles during the process of repeating charge and discharge.
[0033] According to the present invention, the single particle positive electrode active material may be a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn). In this case, the lithium composite transition metal oxide may contain nickel (Ni) in an amount of 60 mol % or 65 mol % or more of all metals other than lithium.
[0034] According to the present invention, the lithium composite transition metal oxide may specifically have a composition represented by the following Chemical Formula 1.
[0035] [Chemical formula 1] Li a Ni b Co c Mn d M 1 e O 2
[0036] In the above Chemical Formula 1, M 1 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.90≦a≦1.1, 0.60≦b<1.0, 0 <c<0.40、0<d<0.40、0≦e≦0.10、b+c+d+e=1である。
[0037] The b means the atomic fraction of nickel among the metal elements excluding lithium in the lithium composite transition metal oxide, and may be 0.60, 0.65, 0.8, or 0.85 or more and 0.95 or 0.98 or less.
[0038] The above c means the atomic fraction of cobalt among the metal elements excluding lithium in the lithium composite transition metal oxide, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less.
[0039] The d refers to the atomic fraction of manganese among the metal elements excluding lithium in the lithium composite transition metal oxide, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less.
[0040] The e is M among the metal elements other than lithium in the lithium composite transition metal oxide. 1 It means the element fraction of an element, and may be 0 or more, 0.02, 0.05, or 0.10 or less.
[0041] Method for producing positive electrode active material The present invention provides a method for producing a single-particulate positive electrode active material, the method including the steps of: (A) mixing a positive electrode active material precursor and a lithium raw material, and primarily baking the mixture at a temperature of 800°C to 1000°C to produce a plastic product, and then secondary baking the plastic product at a temperature lower than the primary baking temperature to produce a single-particulate lithium composite transition metal oxide; (B) mixing the single-particulate lithium composite transition metal oxide with a cobalt raw material to prepare a mixture; and (C) heat-treating the mixture at a temperature of 650°C to 800°C.
[0042] The method for producing the positive electrode active material includes the steps of: (cosα)=α, where α is the angle between the major axis of the crystal grain obtained by EBSD analysis and the lithium migration path. 2 The method for producing a single particle positive electrode active material has a value of 0.5 or more. That is, the method for producing the positive electrode active material is the method for producing the positive electrode active material according to the present invention described above. The positive electrode active material according to the present invention can be produced by appropriately adjusting not only the configuration of the production method described above but also the amount of lithium raw material mixed, the firing time, the firing atmosphere, etc. The method for producing the positive electrode active material will be described in more detail below.
[0043] (A) Step The step (A) is a step of mixing a positive electrode active material precursor and a lithium raw material, primary firing at a temperature of 800°C to 1000°C to prepare a plastic product, and secondary firing the plastic product at a temperature lower than the primary firing temperature to prepare a single-particle lithium composite transition metal oxide. Meanwhile, the plastic product may be crushed before secondary firing for uniformity of firing. When a positive electrode active material precursor and a lithium raw material are mixed and fired in two stages instead of one stage, the deviation between the lithium composite transition metal oxides produced by the crushing process after the primary firing can be reduced. In particular, when the primary firing is performed at a temperature of 800°C to 1000°C and the secondary firing is performed at a temperature lower than the primary firing temperature, the particle structure can be made uniform by the same effect as annealing.
[0044] As a result, when a lithium composite oxide is produced by step (A), not only is a single-particle lithium composite transition metal oxide produced, but there are also advantages in that the deviation during sintering can be reduced to improve productivity, and the particle structure can be made uniform due to an effect similar to that of annealing.
[0045] The single-particulate lithium composite transition metal oxide may be composed of 1 to 50 single crystal particles due to the arrangement of the contraction / expansion direction of the positive electrode active material in the electrode and the lithium migration path during rolling. Specifically, the single-particulate lithium composite transition metal oxide may be composed of 1 or more, 5, 10, 20, 30, 40, or 50 or less single crystal particles. The single crystal particles have an average particle size (D EBSD ) may be 0.1 μm to 10 μm, specifically 0.1 μm or 0.2 μm or more and 5 μm, 8 μm, or 10 μm or less. In this case, it is possible to prevent the slurry (composition for forming a positive electrode active material layer) from coagulating or gelling during the production of the electrode, and it is possible to reduce the occurrence of cracks in the particles during the process of repeating charge and discharge.
[0046] The single particulate lithium transition metal composite oxide may have a cation mixing of 5% or less. The cation mixing value is a value measured to measure the substitution of the position of lithium and other metal ions in the structure, and when it is 5% or less, impurities are few in the particle structure, the structure is stable, and the collapse of the particle structure and the resulting increase in resistance during repeated charging and discharging can be prevented.
[0047] The single particle lithium transition metal composite oxide may contain 20,000 ppm or less of lithium by-products, which results in a small amount of impurities in the produced positive electrode active material, and reduces the aggregation phenomenon of the slurry (composition for forming the positive electrode active material) when producing the positive electrode, improving the process and resulting in improved battery performance.
[0048] The positive electrode active material precursor may be a composite transition metal hydroxide, a composite transition metal oxyhydroxide, or a combination thereof. The positive electrode active material precursor may be a dry-mixed mixture of a nickel source material, a cobalt source material, a manganese source material, and / or a doping source material.
[0049] When the positive electrode active material precursor is a composite transition metal hydroxide or a composite transition metal oxyhydroxide, the positive electrode active material precursor may have a composition represented by, for example, Chemical Formula 2 or Chemical Formula 3 below.
[0050] [Chemical formula 2] Ni b’ Co c’ Mn d’ M 2 e’ (OH) 2
[0051] [Chemical formula 3] Ni b’ Co c’ Mn d’ M 2 e’ O.H.
[0052] In the above Chemical Formula 2 or Chemical Formula 3, M 2 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.60≦b'<1.0, 0 <c’<0.40、0<d’<0.40、0≦e′≦0.10、b’+c’+d’+e’=1である。
[0053] The b' means the atomic fraction of nickel among the metal elements, and may be 0.60, 0.65, 0.8, or 0.85 or more, and 0.95 or 0.98 or less. The c' means the atomic fraction of cobalt among the metal elements, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less.
[0054] The d' means the atomic fraction of manganese among the metal elements, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less. The e' is M among the metal elements. 1 It means the element fraction of an element, and may be 0 or more, 0.02, 0.05, or 0.10 or less.
[0055] The nickel source material, the cobalt source material, the manganese source material, and / or the doping source material may be hydroxides, oxides, carbonates, hydrates, nitrates, chlorides, etc., each containing nickel, cobalt, manganese, or a doping element, and may be used alone or in combination of two or more of them. Specifically, Ni(OH) 2 , NiO, Co(OH) 2 , Co 2 O 3 , Mn 3 O 4 , MnO 2 It may be, but is not limited to, the above.
[0056] The lithium source material may be, for example, lithium-containing carbonate, hydrate, hydroxide, nitrate, chloride, etc., and may be used alone or in combination of two or more of these. Specifically, Li 2 CO 3 , LiOH H 2 O, LiOH, LiNO 3 , LiCl, etc., but are not limited thereto. The lithium source materials may be mixed together before the primary firing, or may be mixed separately before the primary firing and before the secondary firing.
[0057] Meanwhile, in step (A), a doping element-containing raw material may be further mixed in addition to the positive electrode active material precursor and the lithium raw material, and the doping element-containing raw material may include one or more metal elements selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Sn, Y, Zn, Ce, F, P, and S.
[0058] According to the present invention, the primary firing may be performed at a temperature of 800°C or 850°C or more and 900°C, 950°C, or 1000°C or less. In this case, the particles grow large, and a single-particle positive electrode active material can be obtained. On the other hand, if the primary firing temperature is less than 800°C, there is a problem that the positive electrode active material becomes a multi-particle type composed of 50 or more particles, and if it exceeds 1000°C, there is a problem that impurities increase in the positive electrode active material structure.
[0059] According to the present invention, the primary firing may be carried out in an oxygen atmosphere to promote particle growth. The primary firing may be performed for 2 to 12 hours, specifically, 2 or 3 hours or more, 9 hours, 10 hours, or 12 hours or less. When the primary firing time is within the above range, the firing uniformity is ensured, and the firing time is minimized, thereby improving productivity.
[0060] According to the present invention, the secondary firing may be performed at a temperature lower than the primary firing temperature, and the secondary firing may be performed at a temperature of 700° C. to 900° C. Specifically, the secondary firing may be performed at a temperature of 700° C. or more and 800° C., 850° C., or less than 900° C. In this case, impurities in the structure can be minimized by the same effect as annealing.
[0061] According to the present invention, in order to maximize the effect similar to that of annealing, the secondary firing may be performed in an oxygen atmosphere. The secondary firing may be performed for 2 to 12 hours, specifically, 2 or 3 hours or more, 9 hours, 10 hours, or 12 hours or less. When the secondary firing time is within the above range, the uniformity of the produced positive electrode active material is ensured, and the firing time can be minimized to improve productivity.
[0062] (B) Step The step (B) is a step of preparing a mixture by mixing the single-particle lithium transition metal composite oxide prepared in the step (A) with a cobalt source material.
[0063] According to the present invention, in step (B), the single particulate lithium composite transition metal oxide and the cobalt source material may be mixed in a molar ratio of 1:0.0001 to 0.05. Specifically, the molar ratio of the single particulate lithium composite transition metal oxide and the cobalt source material may be 1:0.0001 or 1:0.01 or more, and 1:0.03 or 1:0.05 or less. In this case, by-products formed on the surface of the single particulate lithium composite transition metal oxide during the preparation process can be minimized, which is advantageous in that the performance of the prepared positive electrode active material is improved.
[0064] The cobalt source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc. For example, Co(OH) 2 , Co 2 O 3etc., preferably Co(OH) 2 On the other hand, a highly reactive material such as Co(OH) may be used as the cobalt source material. 3 When cobalt acetate or the like is used, there may be a problem that Co penetrates excessively deep into the coating, resulting in almost no coating portion containing cobalt.
[0065] According to the present invention, the mixing in step (B) may be a dry mixing. That is, the powdered cobalt source material may be simply mixed with the single-particle lithium transition metal composite oxide without using a solvent. In this case, the convenience of the process may be increased and the productivity may be improved.
[0066] Meanwhile, in the step (B), a coating element-containing raw material may be further mixed in addition to the single-particle lithium composite transition metal oxide and cobalt raw material, and the metal element contained in the coating element-containing raw material may be Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Sn, Y, Zn, Ce, F, P, and S. The coating element-containing raw material may be acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide containing the metal element. For example, when the metal element is B, boric acid (H 3 BO 3 ) may also be used.
[0067] (C) Step The step (C) is a step of heat treating the mixture at a temperature of 650°C to 800°C.
[0068] The heat treatment in step (C) may be performed at a temperature of 650°C to 800°C. Specifically, the heat treatment temperature may be 650°C or more, 750°C or less, or 800°C or less. When the heat treatment temperature is within the above range, cobalt ions increase only on the surface of the positive electrode active material, and by-products (e.g., NiO, etc.) present on the surface can be reduced. On the other hand, when the heat treatment temperature is less than 650°C, there is a problem that the cobalt ions cannot sufficiently penetrate the surface of the positive electrode active material, and when it is 800°C or more, there is a problem that the cobalt ions penetrate into the inside of the positive electrode active material, and the effect of reducing by-products present on the surface is reduced.
[0069] According to the present invention, in order to increase the reactivity, the heat treatment may be carried out under an oxygen atmosphere. The heat treatment in step (C) may be performed for 2 to 12 hours, specifically, 2 or 3 hours or more, 9 hours, 10 hours, or 12 hours or less. When the heat treatment time is within the above range, the uniformity of the produced positive electrode active material is ensured, and the firing time is minimized, thereby improving productivity.
[0070] positive electrode The present invention also provides a positive electrode including a current collector and a positive electrode active material layer located on the current collector, the positive electrode active material layer including the single-particle positive electrode active material according to the present invention.
[0071] According to the present invention, when the angle between the lithium migration path of the single particle positive electrode active material and an axis parallel to the upper surface of the current collector is θ, (cosθ) 2 The value may be 0.6 or greater.
[0072] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including the single-particle positive electrode active material according to the present invention. In the positive electrode, when the angle between the lithium migration path of the single-particle positive electrode active material and an axis parallel to the top surface of the current collector is θ, (cosθ) 2 The value of (cosθ) is 0.6 or more.2 The value may be 0.6 or more, 0.7, 0.8, 0.9, or 1 or less.
[0073] The direction in which lithium moves is the (003) plane, and the normal direction of the (003) plane is the c-axis direction (hereinafter, c-axis direction) of the crystal structure, which is the contraction / expansion direction of the crystal of the positive electrode active material. Therefore, under the above conditions, the c-axis direction, which is the contraction / expansion direction of the crystal of the positive electrode active material contained in the positive electrode active material layer, is aligned in a direction perpendicular to the upper surface (or electrode surface) of the current collector. In most batteries, the expansion in a direction perpendicular to the upper surface of the current collector is suppressed by an external case, i.e., the electrode is formed in a planar shape and is resistant to deformation in a direction perpendicular to the surface, so when the c-axis direction, which is the contraction / expansion direction of the crystal of the positive electrode active material contained in the positive electrode active material layer, is aligned in a direction perpendicular to the upper surface (or electrode surface) of the current collector, when the positive electrode according to the present invention is applied to a battery, the expansion of the crystal of the positive electrode active material in the c-axis direction is suppressed by an external case, etc., and the life performance can be improved. On the other hand, (cosθ) 2 If the value is less than 0.6, the c-axis direction, which is the direction of contraction / expansion of the crystals of the positive active material, becomes parallel to the upper surface of the current collector, and an improvement in life performance cannot be expected.
[0074] According to the present invention, the (cosθ) 2 value and (cosα) 2 The difference in value may be 0.2 or less, specifically 0.2 or less, or 0.1 or less. In this case, it is considered that the positive electrode active material contained in the positive electrode according to the present invention has a shape and structure more suitable for the formation of an orientation in the positive electrode. This can further improve the performance of the battery.
[0075] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0076] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material. In this case, the positive electrode active material may be included in an amount of 80 wt% to 99 wt%, more specifically, 85 wt% to 98 wt%, based on the total weight of the positive electrode active material layer. When included in the above content range, excellent capacity characteristics can be exhibited.
[0077] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.
[0078] The binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.
[0079] The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by applying a composition (slurry) for forming a positive electrode active material layer, which is manufactured by dissolving or dispersing the positive electrode active material, and optionally a binder and a conductive material in a solvent, onto a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above. Alternatively, the positive electrode may be manufactured by casting the composition for forming a positive electrode active material layer onto another support, peeling it off from the support, and laminating the film obtained on the positive electrode current collector.
[0080] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.
[0081] Lithium secondary battery The present invention also provides an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0082] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is the same as that described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0083] The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0084] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to strengthen the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0085] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material. The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), SnO 2, vanadium oxide, lithium vanadium oxide, or other metal oxide capable of doping and dedoping lithium; or a composite containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, either low-crystalline carbon or high-crystalline carbon may be used as the carbon material. Typical low-crystalline carbons are soft carbon and hard carbon, and typical high-crystalline carbons are amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbons such as petroleum or coal tar pitch derived cokes. The negative electrode active material may be contained in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.
[0086] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0087] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0088] The negative electrode active material layer is produced by applying a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the composition. Alternatively, the composition for forming a negative electrode active material layer may be cast onto another support, and then peeled off from the support to obtain a film, which is then laminated onto the negative electrode current collector.
[0089] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation, and it is particularly preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.
[0090] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0091] Specifically, the electrolyte may include an organic solvent and a lithium salt. The organic solvent may be any solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among them, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant capable of improving the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9 to provide excellent electrolyte performance.
[0092] The lithium salt can be any compound capable of providing lithium ions used in lithium secondary batteries without any particular limitation. 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 etc. may be used. The concentration of the lithium salt is preferably within the range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, and therefore can exhibit excellent electrolyte performance, allowing lithium ions to migrate effectively.
[0093] In addition to the constituents of the electrolyte, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.
[0094] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics, and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs), etc.
[0095] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same. The battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0096] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0097] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery in a medium- to large-sized battery module including a plurality of battery cells. EXAMPLES
[0098] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;
[0099] Examples and Comparative Examples Example 1 Ni 0.95 Co 0.03 Mn 0.02 (OH) 2 The composition is represented by the average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05 and subjected to primary firing at a temperature of 850° C. for 9 hours in an oxygen atmosphere to produce a plastic product. The plastic product was crushed and then subjected to secondary firing at a temperature of 750° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.95 Co 0.03 Mn 0.02 O 2 A single particle lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0100] The produced single-particle lithium composite transition metal oxide was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a single particle positive electrode active material.
[0101] Example 2 Ni 0.88 Co 0.03 Mn 0.09 (OH) 2 The composition is represented by the average particle size (D 50A positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and the mixture was subjected to primary firing at a temperature of 880° C. for 9 hours in an oxygen atmosphere to produce a plastic product. The plastic product was crushed and then subjected to secondary firing at a temperature of 780° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.88 Co 0.03 Mn 0.09 O 2 A single particle lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0102] The produced single-particle lithium composite transition metal oxide was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a single particle positive electrode active material.
[0103] Example 3 Ni(OH) 2 , Co 2 O 3 , and MnO 2 The mixture was mixed to a molar ratio of Ni:Co:Mn = 95:2:3, and LiOH was mixed to a molar ratio of (Ni+Co+Mn):Li = 1:1.05. The mixture was subjected to primary firing at a temperature of 890 °C for 9 hours in an oxygen atmosphere to produce a plastic product. The plastic product was crushed and then subjected to secondary firing at a temperature of 780 °C for 9 hours in an oxygen atmosphere to produce LiNi 0.95 Co 0.03 Mn 0.02 O 2 A single particle lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0104] The produced single-particle lithium composite transition metal oxide was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a single particle positive electrode active material.
[0105] Example 4 Ni(OH) 2 , Co2 O 3 , and MnO 2 The mixture was mixed to a molar ratio of Ni:Co:Mn = 95:2:3, and LiOH was mixed to a molar ratio of (Ni+Co+Mn):Li = 1:1.05. The mixture was subjected to primary firing at a temperature of 860 °C for 9 hours in an oxygen atmosphere to produce a plastic product. The plastic product was crushed and then subjected to secondary firing at a temperature of 760 °C for 9 hours in an oxygen atmosphere to produce LiNi 0.95 Co 0.03 Mn 0.02 O 2 A single particle lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0106] The produced single-particle lithium composite transition metal oxide was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a single particle positive electrode active material.
[0107] Example 5 Ni 0.88 Co 0.03 Mn 0.09 (OH) 2 The composition is represented by the average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05 and subjected to primary firing at a temperature of 880° C. for 9 hours in an oxygen atmosphere to produce a plastic product. The plastic product was crushed and then subjected to secondary firing at a temperature of 800° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.95 Co 0.03 Mn 0.02 O 2 A single particle lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0108] The produced single-particle lithium composite transition metal oxide was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a single particle positive electrode active material.
[0109] Example 6 Ni 0.88 Co 0.03 Mn 0.09 (OH) 2 The composition is represented by the average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and the mixture was subjected to primary firing at a temperature of 850° C. for 9 hours in an oxygen atmosphere to produce a plastic product. The plastic product was crushed and then subjected to secondary firing at a temperature of 780° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.88 Co 0.03 Mn 0.09 O 2 A single particle lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0110] The produced single-particle lithium composite transition metal oxide was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a single particle positive electrode active material.
[0111] Comparative Example 1 Ni 0.95 Co 0.03 Mn 0.02 (OH) 2 The composition is represented by the average particle size (D 50 The positive electrode active material precursor having a diameter of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and calcined at 750° C. for 9 hours in an oxygen atmosphere to obtain LiNi 0.95 Co 0.03 Mn 0.02 O 2 A lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0112] The lithium composite transition metal oxide thus produced was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a secondary particle-like positive electrode active material.
[0113] Comparative Example 2 Ni 0.88 Co 0.03 Mn 0.09 (OH) 2 The composition is represented by the average particle size (D 50 The positive electrode active material precursor having a diameter of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and calcined at 800° C. for 9 hours in an oxygen atmosphere to obtain LiNi 0.88 Co 0.03 Mn 0.09 O 2 A lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0114] The lithium composite transition metal oxide thus produced was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a secondary particle-like positive electrode active material.
[0115] Comparative Example 3 Ni 0.88 Co 0.03 Mn 0.09 (OH) 2 The composition is represented by the average particle size (D 50 The positive electrode active material precursor having a diameter of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and calcined at a temperature of 840° C. for 9 hours in an oxygen atmosphere to obtain LiNi 0.88 Co 0.03 Mn 0.09 O 2 A lithium transition metal composite oxide having a composition represented by the following formula was produced.
[0116] The lithium composite transition metal oxide thus produced was mixed with powdered Co(OH) 2 (Huayou Cobalt Co., Ltd.) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700° C. for 5 hours in an oxygen atmosphere to prepare a secondary particle-like positive electrode active material.
[0117] Experimental Example Experimental example 1: EBSD analysis (Production of positive electrodes) The positive electrode active materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3, carbon black (Denka Black, Denka Corporation) conductive material, and PVdF (Kureha, KF1300) binder were added to an N-methylpyrrolidone (NMP) (Daejung Chemicals & Metals) solvent in a weight ratio of 95:3:2 to prepare compositions for forming a positive electrode active material layer.
[0118] The positive electrode active material layer-forming composition was applied to one side of an aluminum foil current collector having a thickness of 20 μm, and dried at a temperature of 135° C. for 3 hours to form a positive electrode active material layer. 3 The mixture was rolled by a roll press method to prepare a positive electrode.
[0119] For reference, electrode density is the mass of the positive electrode active material per unit area of the electrode (excluding the weight of the conductive material, binder, and current collector) divided by the unit volume of the electrode (thickness excluding the current collector x unit area).
[0120] (EBSD analysis) Using HITACHI's IM5000 (accelerating voltage: 6 kV), the positive electrode was irradiated with an argon (Ar) ion beam and cut by an ion milling method to obtain a cross section of the positive electrode, and using JEOL's JSM-7900F (accelerating voltage: 20 kV), the cross section of the positive electrode was measured and analyzed. As the image processing-EBSD quantification analysis software, AztecCrystal from OXFORD Instruments was used.
[0121] 1 is an EBSD Band Contrast (BC) image of a cross section of a positive electrode containing the positive electrode active material of Example 1, in which a crystal grain model based on crystal orientation is displayed as a hexagonal column. In the EBSD BC image, the vertical direction (Y1) is the direction perpendicular to the electrode, and the horizontal direction (X1) is the direction parallel to the electrode.
[0122] Referring to FIG. 1, it can be seen that the single-particle positive electrode active material is composed of single crystal particles, and that the major axis direction of the single-particle positive electrode active material particles is aligned in a direction parallel to the electrode.
[0123] FIG. 2(a) is an SEM image of a cross section of a positive electrode including the positive electrode active material of Comparative Example 1, and FIG. 2(b) is an EBSD Band Contrast (BC) image of a cross section of a positive electrode including the positive electrode active material of Comparative Example 1.
[0124] Referring to FIG. 2, it can be seen that the positive electrode active material of Comparative Example 1 is in the form of secondary particles in which hundreds of primary particles are aggregated, and that randomly arranged primary particles exist within the secondary particles.
[0125] The angle between the long axis of all crystal grains (approximately 50 to 100 grains) in the image obtained by EBSD analysis and the lithium migration path is defined as α, and the (cosα) of each crystal grain is 2 The average values are shown in Table 1 below. (cosθ) 2 The closer the value is to 1, the more parallel the long axis of the crystal grain is to the lithium migration path.
[0126] The angle between the c-axis direction vector (Euler angle) of all crystal grains (approximately 50 to 100 grains) in the image obtained by EBSD analysis and the direction vector perpendicular to the electrode (= the angle between the lithium migration path (Li path) and the direction vector parallel to the electrode) is defined as θ, and the (cosθ) of each crystal grain is 2 The values were calculated and the average values are shown in Table 1 below, and the degree of alignment of the electrode with the lithium transport path of the positive electrode active material was confirmed.
[0127] Figure 3 shows the angle between the c-axis vector (Euler angle) of the crystal grain and the vector perpendicular to the electrode (= the angle between the lithium migration path (Li path) and the vector parallel to the electrode), and (cosθ) 2 It is considered that the closer the value is to 1, the more parallel the lithium migration path is to the electrode surface direction.
[0128] [Table 1] [Table 1]
[0129] Experimental Example 2: Evaluation of battery characteristics (Half-cell manufacturing) The positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, carbon black (Denka Black, Denka Corporation) conductive material, and PVdF (Kureha, KF1300) binder were added in a weight ratio of 95:3:2 to an N-methylpyrrolidone (NMP) (Daejung Chemicals & Metals) solvent to prepare compositions for forming positive electrode active material layers.
[0130] The positive electrode active material layer-forming composition was applied to one side of an aluminum foil current collector having a thickness of 20 μm, and dried at a temperature of 135° C. for 3 hours to form a positive electrode active material layer. Next, the positive electrode active material layer was rolled using a roll press method so that the porosity of the rolled positive electrode active material layer was 20% by volume, thereby manufacturing a positive electrode. A half-cell was fabricated using the positive electrode and lithium metal as the negative electrode.
[0131] (1) Evaluation of initial resistance (DCIR) The half-cells prepared above were charged at 25° C. at a constant current (CC) of 0.2 C up to 4.25 V, then charged at a constant voltage (CV) of 4.25 V until the charging current reached 0.05 mAh (cut-off current), and then discharged at a constant current of 0.2 C for 10 seconds. The initial resistance was calculated by dividing the voltage difference between when the battery was fully charged and when 10 seconds had elapsed since the start of discharge by the current, and the results are shown in Table 2 below.
[0132] (2) Evaluation of capacity retention rate and resistance increase rate The half-cells prepared above were charged at 25° C. at a constant current (CC) of 0.2 C up to 4.25 V, then charged at a constant voltage (CV) of 4.25 V until the charging current reached 0.05 mAh (cut-off current), and then left for 20 minutes, after which they were discharged at a constant current of 0.2 C down to 2.5 V.
[0133] The cell was then transferred to a chamber at 45°C, charged to 4.25V at a constant current of 0.33C, then charged at a constant voltage (CV) of 4.25V until the charge current reached 0.05mAh (cut-off current), and then discharged to 2.5V at a constant current of 0.33C, with 30 cycles of charge and discharge being performed. At this time, the percentage of the discharge capacity at the 30th cycle relative to the discharge capacity at the first cycle was taken as the capacity retention rate, and is shown in Table 2 below. In addition, the percentage of the DCIR value at the 30th cycle relative to the DCIR value at the first cycle was taken as the resistance increase rate, and is shown in Table 2 below. For reference, the DCIR value at the nth cycle was calculated by dividing the voltage difference between the fully charged state and 10 seconds after the start of discharge, obtained by discharging to 2.5V at a constant current of 0.33C in the nth cycle, by the current.
[0134] [Table 2] [Table 2]
[0135] With reference to Tables 1 and 2, the positive electrode active materials of Examples 1 to 6 have a single particle shape in which the long axis of the crystal grains and the lithium migration path are aligned in parallel, and as a result, the lithium migration path and the electrode surface direction in the battery containing them are parallel, and it can be seen that this can improve the initial resistance characteristics and life characteristics of the battery. In contrast, the positive electrode active materials of Comparative Examples 1 and 2 are in the form of secondary particles in which hundreds of primary particles are aggregated, and randomly arranged primary particles exist within the secondary particles, and it can be confirmed that the initial resistance characteristics and life characteristics of the battery are significantly worse than those of Examples 1 to 6. In addition, the positive electrode active material of Comparative Example 3 exists in a state in which the secondary particles in which hundreds of primary particles are aggregated and the single particle shape are mixed, and it can be confirmed that the initial resistance characteristics and life characteristics of the battery are significantly worse than those of Examples 1 to 6.
Claims
1. When the angle between the long axis of the crystal grain obtained by electron backscatter diffraction (EBSD) analysis and the lithium migration path is α, (cosα) 2 A single-particle positive electrode active material having a value of 0.5 or more.
2. 2. The single-particle positive electrode active material according to claim 1, which consists of 1 to 50 single crystal particles.
3. The single crystal particles have an average particle size (D EBSD 3. The positive electrode active material according to claim 2, wherein the particle diameter is 0.1 μm to 10 μm.
4. (A) mixing a positive electrode active material precursor and a lithium raw material, and first baking the mixture at a temperature of 800° C. to 1000° C. to produce a plastic product, and then secondarily baking the plastic product at a temperature lower than the first baking temperature to produce a single-particle lithium composite transition metal oxide; (B) mixing the single-particle lithium composite transition metal oxide with a cobalt source material to prepare a mixture; (C) heat treating the mixture at a temperature of 650° C. to 800° C.; The method for producing a single-particulate positive electrode active material includes the steps of:
5. The method for producing a single-particle positive electrode active material according to claim 4 , wherein the primary firing in step (A) is performed in an oxygen atmosphere.
6. The method for producing a single-particle positive electrode active material according to claim 4, wherein the secondary firing in step (A) is performed at a temperature of 700°C to 900°C.
7. The method for producing a single-particle positive electrode active material according to claim 4 , wherein the secondary firing in step (A) is performed in an oxygen atmosphere.
8. 5. The method for producing a single-particle positive electrode active material according to claim 4, wherein in step (B), the single-particle lithium composite transition metal oxide and the cobalt raw material are mixed in a molar ratio of 1:0.0001 to 0.
05.
9. The method for producing a single-particulate positive electrode active material according to claim 4 , wherein the mixing in step (B) is a dry mixing.
10. The method for producing a single-particle positive electrode active material according to claim 4 , wherein the heat treatment in step (C) is performed in an oxygen atmosphere.
11. A current collector; a positive electrode active material layer located on the current collector, The positive electrode active material layer comprises the single-particle positive electrode active material according to any one of claims 1 to 3.
12. When the angle between the lithium migration path of the single particle positive electrode active material and the axis parallel to the upper surface of the current collector is θ, (cos θ) 2 12. The positive electrode of claim 11, wherein the value is 0.6 or greater.
13. The (cosθ) 2 value and (cos α) 2 The positive electrode of claim 12 , wherein the difference in value is 0.2 or less.
Citation Information
Patent Citations
All-solid-state lithium battery
WO2018025594A1
Positive electrode active material precursor for secondary battery, positive electrode active material, and lithium secondary battery comprising same
WO2021154021A1
Method for preparing cathode active material for lithium secondary battery and cathode active material prepared thereby
WO2022075748A1